Marine algae of Perak Island, Jarak Island and the Sembilan Group of Islands in the Straits of Malacca - Siew-Moi, Phang,; Phaik-Eem, Lim,; Jillian Lean Sim, Ooi,; Hui-Yin, Yeong,; Woan-Shien, Ng, (Malaysian Journal of Science, 2008)
A preliminary checklist of marine algae from Pulau Jarak, Sembilan Group of Islands and Pulau Perak in the Straits of Malacca was compiled from two expeditions. The checklist of a total of 66 taxa, comprises one family of Cyanophyta with two genera and six taxa, seven families of Chlorophyta with 11 genera and 18 taxa, 12 families of Rhodophyta with 20 genera and 39 taxa, and two families of Phaeophyta with three genera and three taxa. One new record Lyngbya confervoides f. violacea is reported for the first time for Malaysia. The three islands have a low similarity in marine algal diversity.